Study on The Addition of Honey as a Natural Antimicrobial Agents in Avocado Juice (Persea americana Mill) - Suhartatik, Nanik; Mustofa, Akhmad; Wijaya, Danastri; ES, Eko Yuliastuti; Astuti, Beti Cahyaning (Green Engineering Society, 2024)
Unpasteurized avocado juice is a popular food product, considered natural, fresh, and healthy. Microbial contamination in unpasteurized juice is high and can pose health risks to humans. Such processing technology is applied to reduce the level of contamination, such as pasteurization, adding preservatives, cooling/freezing temperature, or adding antimicrobial compounds. Honey has a high sugar content, low pH, contains hydrogen peroxide, and organic acid that can inhibit the growth of pathogenic bacteria. This research aims to determine the antibacterial activity of honey in avocado juice using different types of honey types including honey produced by Apis dorsata (AD), Apis mellifera from wildflowers (AMW), Trigona sp (TG) and A. mellifera from kapok (Ceiba pentandra) (AMC) flowers). The second factor was honey concentration (5, 10, and 15%). The results showed that after 2h of incubation, AD honey inhibited the total coliform bacteria by 98.84% at a concentration of 10%, AMW honey effectively inhibited total Staphylococci by 99.04% at a concentration of 15%, and TG honey successfully inhibited total Salmonella-Shigella bacteria at a concentration of 15%. Therefore, using honey in avocado juice can inhibit the growth of pathogenic bacteria, although it has not reached the minimal limits of fruit juice quality standards. Further research is needed to determine the minimum inhibitory concentration of honey required to inhibit pathogenic bacteria in avocado juice.